The role of local government units in increasing access to therapeutic rehabilitation services for patients with musculoskeletal diseases - Sobczyk, Karolina; Grajek, Mateusz; Woźniak-Holecka, Joanna (Journal of Education, Health and Sport, 2022)
Chronic diseases of the osteoarticular and muscular system belong to a group of health problems that lead to a limitation of the organism's efficiency, making it difficult or impossible for individuals to function normally. Of the forms of treatment used for chronic diseases of the osteoarticular system, rehabilitation is by far the most common. These activities are mainly financed by the National Health Fund, as well as by social insurance. A complementary role is played by local governments that finance medical rehabilitation for their residents in the form of health policy programmes, implemented as public health tasks. An important argument in favour of rehabilitation at the self-governmental level is the long waiting time for medical rehabilitation services financed by the National Health Fund. The aim of the paper was to show the role of local government in increasing access to therapeutic rehabilitation services for patients with musculoskeletal diseases. The paper discusses such issues as the importance of musculoskeletal diseases for the efficiency of individuals, organization and financing of guaranteed services in curative rehabilitation, as well as increasing access to these services at the local government level.